Cyril of Alexandria's critique of the term Theotokos by Nestorius Constantinople - E. Artemi (Acta Theologica)
The God Word became truly human. He had the real human nature (body and soul), but without propensity to sin. Jesus Christ was the incarnate Word of God. He was born of the Virgin Mary and conceived by the Holy Spirit. His divinity is manifest in the extraordinary circumstances of His birth and, in particular, in the preservation of the virginity of the Theotokos. His humanity is guaranteed in that He was born of a woman, a real historical person. Nestorius of Constantinople rejected the title Theotokos for the mother of the incarnated Word. He insisted that Mary as a human being could give birth only to a human being, and not to God. He persisted in calling the Virgin Mary Christotokos. This teaching jeopardised the salvation of the human race. Cyril of Alexandria disproved this erroneous belief and supported the reason why the mother of God should be called Theotokos.